2018
DOI: 10.3389/fpls.2018.01841
|View full text |Cite
|
Sign up to set email alerts
|

A Trade-Off Between Sporangia Size and Number Exists in the Potato Late Blight Pathogen Phytophthora infestans, and Is Not Altered by Biotic and Abiotic Factors

Abstract: The negative relationship between offspring size and number is a classic example of trade-off between life-history traits, reported many times in animal and plant species. Here, we wanted to ascertain whether such a trade-off occurred in the oomycete Phytophthora infestans, and whether it was impacted by biotic and abiotic factors. We thus conducted three infection experiments under controlled conditions and measured the number and the size of sporangia (asexual propagules) produced on potato by different P. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In most pathosystems, an increase in temperature is positively associated with aggressiveness [ 32 , 33 ]. As environmental conditions and host genotype usually strongly correlate with disease [ 34 ], the host genotype factor with three levels (reference line B37, susceptible line Sus1, and the hybrid Niklas ® ) was included in the experimental design. Interestingly, an interaction between isolate origin and host genotype was observed for the variable AUDPC.…”
Section: Discussionmentioning
confidence: 99%
“…In most pathosystems, an increase in temperature is positively associated with aggressiveness [ 32 , 33 ]. As environmental conditions and host genotype usually strongly correlate with disease [ 34 ], the host genotype factor with three levels (reference line B37, susceptible line Sus1, and the hybrid Niklas ® ) was included in the experimental design. Interestingly, an interaction between isolate origin and host genotype was observed for the variable AUDPC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, given that soil pathogens are patchily distributed (G omez-Aparicio et al 2012), it is possible that we were not successful at including the relevant pathogens of native forest species in our experiment. It is also possible that spores and other dispersal units of fungal and oomycete pathogens may have not passed through the fine mesh we used to produce the microbial filtrates because of their larger size (Mariette et al 2018). If the absence of significant negative feedback among native species is not an artifact of our experimental design, the weakening of this stabilizing force to species coexistence may lead to the decay in diversity of an already species-depauperate tree community.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Mariette et al (2018) explored whether a negative relationship between progeny size and number occurred in the late blight oomycete, Phytophthora infestans, and whether the tradeoff was impacted by potato cultivar or host of origin of the pathogen (tomato and potato). They showed that this trade-off was not changed by these biotic factors, suggesting that the observed polyphenism for these traits in P. infestans populations will favour the coexistence of distinct reproductive strategies.…”
Section: Hos T Pl Ant Re S Is Tan Ce Recep Tivit Y and Multi -Infec Tion Pro Ce Ss E Smentioning
confidence: 99%